Mini Cleanroom for the Manufacture of Advanced Therapy Medicinal Products (ATMP): Bioengineered Corneal Epithelium - Silvia Berisa-Prado; Natalia Vázquez; Manuel Chacón; Mairobi Persinal-Medina; Sergio Alonso-Alonso; Begoña Baamonde; José F. Alfonso; Luis Fernández-; Jesús Merayo-Lloves; Álvaro Meana (MDPI AG, 2021)
Among several requirements for the manufacture of Advanced Therapy Medicinal Products (ATMP) are: following the guidelines of a pharmaceutical quality system, complying with Good Manufacturing Practice (GMP) and access to a cleanroom fulfilling strict environmental conditions (Class A work area and Class B environment). This makes ATMP expensive. Moreover, the production of many of these therapeutic products may also be unprofitable, as in most cases their use is limited to a few patients and to a single batch per manufacturing unit. To reduce costs, ATMP may be produced in a scaled-down system isolated from the external environment (isolator), allowing for placement of this facility in a Class D environment, which is much more permissive and less costly. In this work, we confirm that it is possible to manufacture bioengineered corneal epithelium inside an isolator while fulfilling all the safety assurance standards at an affordable cost for patients. This small-scale ultra-clean working environment complies with GMP guidelines and could be a solution for the high costs associated with conventional cleanroom ATMP production.